Memberikan Edukasi Pentingnya Minat Belajar terhadap Anak Yayasan Pembangun Didikan Islam Indonesia - Fahriza, Tasya; Atika, Tuti; Ritonga, Fajar Utama (Medan Resource Center, 2024)
Learning interest is a crucial factor in children's educational development. This study aims to provide education on the importance of learning interest to children at the Yayasan Pembangun Didikan Islam Indonesia (Indonesian Islamic Education Development Foundation). Learning interest can be defined as a high inclination and enthusiasm or a strong desire towards something one wishes to learn. With learning interest, children tend to be more focused and enthusiastic in engaging with the learning process. This educational activity was conducted at the Yayasan Pembangun Didikan Islam Indonesia, located at Jl. Jamin Ginting No. 271, Padang Bulan, Kec. Medan Baru, Medan City, North Sumatra 20157. Through various interactive and enjoyable methods, the research team endeavored to instill in children an understanding of the benefits and importance of having a high learning interest. In this activity, children were encouraged to understand that learning is not merely an obligation, but can also be an enjoyable and beneficial activity for their personal development. Various educational activities were designed to help children discover areas that interest them, thereby naturally increasing their learning motivation. The results of this educational activity are expected to increase children's awareness of the importance of learning interest, which in turn will positively impact their academic achievement and personal potential development. Additionally, this activity aims to provide caregivers and educators at the foundation with an understanding of effective ways to cultivate and maintain children's learning interest. Through this education, it is hoped that children at the Yayasan Pembangun Didikan Islam Indonesia can develop a strong learning interest, which will serve as an important foundation for their educational success and future.